Cellular Variant of Focal Segmental Glomerulosclerosis Treated with Plasma Exchange - Cunha, L (2017)
Focal segmental glomerulosclerosis (FSGS) is the most common primary glomerular disease in nephrotic patients in the United States, frequently leading to end stage renal disease (ESRD). The cellular variant is a rare form of FSGS commonly associated with poor outcome. We report a case of cellular variant FSGS with progressive kidney dysfunction successfully treated with plasma exchange (PE). A 49-year-old Caucasian female presented with two days of ankle edema and hypertension. Laboratory findings showed serum creatinine (SCr) 1.6 mg/dL, urine albumin/creatinine ratio (uACR) 2.8 g/g, haematuria 3+ and no immunological abnormalities. Kidney biopsy revealed a cellular FSGS variant with segmental endocapillary proliferation on light microscopic, negative immunofluorescence and widespread foot process effacement by electronic microscopic. Prednisolone 1 mg/Kg was started. Four days later the SCr worsened (3.6 mg/dL) and the patient became severely nephrotic with uACR of6.8g/g, quickly attaining a maximum of 24.6 g/g in a short time and albumin of 2.15g/dL. Pulsed methyl prednisolone was started. Despite a 10 course of steroids, no clinical improvement was observed. Considering the rapidly worsening renal function and severe nephrotic syndrome, PE was begun in association with mycophenolate mofetil and tacrolimus. Kidney function recovered after one week. Complete remission was achieved at 3rd week and remains in complete remission at 27 months follow-up. Prolonged remission is a challenge in primary FSGS. PE associated with combined immunosuppression was effective in the present case. The short and long-term effects of plasma exchange in primary FSGS should be evaluated in prospective studies.